2015
DOI: 10.1038/jp.2015.147
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for enhancing psychosocial support of NICU parents through staff education and support

Abstract: Providing psychosocial support to parents whose infants are hospitalized in the neonatal intensive care unit (NICU) can improve parents' functioning as well as their relationships with their babies. Yet, few NICUs offer staff education that teaches optimal methods of communication with parents in distress. Limited staff education in how to best provide psychosocial support to families is one factor that may render those who work in the NICU at risk for burnout, compassion fatigue and secondary traumatic stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(82 citation statements)
references
References 120 publications
0
71
0
5
Order By: Relevance
“…Clearly, more research is needed to identify further antecedents of professional quality of life in neonatal nurses. Furthermore, there is a need for research designed to confirm the proposed benefits of education, support and training interventions in restoring, maintaining and enhancing neonatal nurses’ professional quality of life (Braithwaite, ; Hall et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Clearly, more research is needed to identify further antecedents of professional quality of life in neonatal nurses. Furthermore, there is a need for research designed to confirm the proposed benefits of education, support and training interventions in restoring, maintaining and enhancing neonatal nurses’ professional quality of life (Braithwaite, ; Hall et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Training NICU nurses to use person-centred communication skills has been reported to be effective in reducing parental stress without the use of any particular communicative intervention. However, Hall et al (35) found that NICU nurses might not be trained in communication with parents in distress and therefore not prepared to respond to parents' stress and meet their psychosocial needs. In the present study, all staff in the NICU received training in person-centred communication before the start of the study, but one limitation of the introduction might have been that the nurses at the NICU did not have the possibility to use the new communication style for a longer period of time before the study started.…”
Section: Discussionmentioning
confidence: 99%
“…enhanced staff training during orientation), the qualitative data make clear the fact that FCC should ideally be a part of ongoing education for staff working in NICU. It is recognised in the literature that NICU staff working in a highly stressful environment need ongoing support, education and tools in order to be able to provide FCC and adequate support to families . We therefore intend to continue integrating FCC into the unit and engaging and training staff in the benefits of FCC.…”
Section: Discussionmentioning
confidence: 99%